STATUS KEBERLANJUTAN SISTEM PENGEMBANGAN PENYULUHAN PERIKANAN ERA DESENTRALISASI DI INDONESIA - Anthon A. Djari; Sugeng Hari Wisudo; Rudi C. Tarumengkeng; Hartrisari Hardjomidjojo; Basita Ginting (Institut Pertanian Bogor, 2009)
This examination forwarded to identify the kind of atributes that reflecting the fisheries exten-sion development and analizing the fisheries present status in some region in Indonesia. Data collecting method implemented during the field survey process, and also literature tracement as the secondary date. This study employs the multi dimensional scaling for the analizing method as the examination of the fisheries present status. Based on the result we know that the sustainability sta-tus of fisheries extension system in decentralize circumstance majority in sustainable condition, except on equipment dimension. Key words: decentralize circumstance, development system, extension fisheries, sustainability status